2021
DOI: 10.17770/sie2021vol4.6294
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Performance in Speed Climbing: Accuracy of the Force-Velocity Test on a Cycle Ergometer

Abstract: The present study examined the validity of the force-velocity (F-V) mechanical parameters of the lower limbs as a predictors of the competitive performance in junior male speed climbing. The second aim was to evaluate F-V characteristics in competitive speed climbers in the junior male category. Ten junior male speed climbers (age: 18±0.5 years; BH: 174.7±4.5 cm; BW: 66.4±6.6 kg; with mean best climbing time from the competition BCT: 7.29±0.66 s) were participants in the research. All they were participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The extent to which this procedure correlates with performance in speed climbing has not yet been investigated in detail. Another approach, the Wingate test on a bicycle ergometer, has not been shown to correlate with times achieved in speed climbing (26). In contrast, Krawczyk et al have demonstrated in several studies that an assessment based on a countermovement jump strongly correlates with time in speed climbing (13, 16, 27-29).…”
Section: Physiologymentioning
confidence: 98%
See 2 more Smart Citations
“…The extent to which this procedure correlates with performance in speed climbing has not yet been investigated in detail. Another approach, the Wingate test on a bicycle ergometer, has not been shown to correlate with times achieved in speed climbing (26). In contrast, Krawczyk et al have demonstrated in several studies that an assessment based on a countermovement jump strongly correlates with time in speed climbing (13, 16, 27-29).…”
Section: Physiologymentioning
confidence: 98%
“…In order to assess the performance in speed climbing, it is perhaps even more suitable to look at the velocity of the COM, since climbers ascend continuously and as fast as possible. Male and female elite climbers have average vertical velocities of 2.5 m/s and 2 m/s respectively (26).…”
Section: Biomechanical Metrics Characterising Movement Qualitymentioning
confidence: 99%
See 1 more Smart Citation